Combining sensory evaluation and mental models in the assessment of consumer preferences for and choice of healthy products: experience from a field experiment in Kenya. - Okello, J.J.; Lagerkvist, Carl Johan; Muoki, Penina Ngusye; Heck, S.; Prain, Gordon (2016)
This paper combines Just-About-Right (JAR) sensory evaluation and means-end chain (MEC) analysis to examine consumer evaluation of the sensory attributes of conventionally bred biofortified orange-fleshed sweetpotato (OFSP). It specifically examined the role of information on biofortification process on consumers’ expected and actual sensory evaluation of OFSP attributes and the mental models associated with the decision to consume OFSP. It is based on data collected via a field experiment with 501 rural consumers. Each consumer was randomly placed into one of the 3 treatment groups and received: i) general information about biofortification (Control), ii) general and positive information (Treatment 1) and iii) general and negative information (Treatment 2). The study finds, among others, that information on vitamin A (i.e., nutrition), taste and texture were, overall, discriminated by the kind of information provided (i.e., treatment), with texture being considered to be at an inappropriately lower level. Nutrition attribute was, however, considered to be at a higher than appropriate level. The results of the MEC were in line with those of sensory evaluation, with mental constructs (and models) being strongly discriminated by treatment type. It concludes that information consumers receive affect the expected and actual sensory evaluation OFSP attributes and mental models of OFSP consumption. We highlight some implications of these findings.